Registro de Marcas – Aspectos distintivos e suas aplicações - Siqueira, Joelson Ramos de (2021)
The importance of trademark registration as a marketing tool becomes fundamental and is capable of attributing a strategic position to its holder, in addition to composing the intangible assets. The distinction of the products and services identified by it confers quality and origin, being its referential scope of the identity of its holder. In this way, the correct understanding of the distinction of the institutes "invented name", "domain registration name" and "registered trademark" from the scopes of validity, scope, certification and legal aspects, show the primordial and broad function of the certification of the trademark registration. The present study had an exploratorydescriptive character, based on a literature review in primary and secondary data sources, to substantiate scientific articles and documentary analysis of the legislation, as well as the analysis of regulations issued by the registration and research agency in collections and database. In this sense, we present a history of trademark law and its contextualization in industrial property law, emphasizing the genesis of its functions and its transformation over time with a view to the demand of society. These functions and characteristics of brands end up showing their relevance in the early days of markets, as well as in modern market practices today. The form of acquisition of the right to ownership of brands with a declaratory bias adopted by national law confers the brand the ability to compose the property of its owner. Thus, in order to understand the local panorama of trademark registration, we surveyed the trademark registrations of members of the Guarapuava Commercial and Business Association (ACIG) at the National Institute of Intellectual Property (INPI). Finally, we systematized a script in the form of a digital booklet about the application for trademark registration, in order to clarify and facilitate the registration of their trademarks for owners. Thus, it was possible to verify that the construction of the brand is fundamental for the marketing aspect and its safeguard will only be possible through registration. And in a highly competitive market, the trademark becomes a primary tool for online advertising and commerce.